Divergent evolutionary dynamics of benign and malignant tumors - George Butler; Joanna Baker; Sarah R. Amend; Kenneth J. Pienta; Chris Venditti (Proceedings of the National Academy of Sciences, 2025)
Benign and malignant (cancerous) tumors differ markedly in their impact on organismal fitness, yet studies in comparative oncology rarely distinguish between them. Using a Bayesian phylogenetic framework across birds and mammals, we show that while both tumor types increase in prevalence with body mass, only the prevalence of malignant tumors is negatively associated with the rate of body size evolution—suggesting that adaptive mechanisms of cancer defense are associated with rapidly evolving lineages. Additionally, the rate of lineage diversification is positively associated with the prevalence of both tumor types in birds but not mammals, potentially reflecting differences in genome architecture and speciation dynamics. Together, these results highlight distinct macroevolutionary drivers of benign versus malignant tumor prevalence and underscore the value of treating tumor types separately in comparative oncology.